Design for the real world : the case study of fish-ball seller cart / Fitorio Bowo Leksono and Hari Nugraha - Leksono, Fitorio Bowo; Nugraha, Hari (Universiti Teknologi MARA, Perak, 2021)
Design has been known for its potential to solve problem outside of design industries, and one of them is the lack of competitiveness of micro businesses in Indonesia. This project will serve as the example on how design, through Design Thinking method could increase the competitiveness through adding value of the business in the form of well design bike cart. The micro business that become the object of this project is a fish ball street vendor in Bekasi town, Indonesia. The outcome of this project is the prototype of the cart that will be used by the user on his daily selling activity.